Aborted Sudden Cardiac Death and a Mother with Suspected Metabolic Myopathy. Issue 8 (January 2014) - Finsterer, Josef; Stöllberger, Claudia; Keller, Hans
Aborted sudden cardiac death (SCD) has not been reported as initial manifestation of cardiac involvement in metabolic myopathy (MM). A 20-year-old female with a previous history of three syncopes, hyperhidrosis, and recurrent tick bites experienced aborted SCD. Her mother presented with MM, and a history of pituitary adenoma, nephroptosis, arterial hypertension, depression, migraine, goiter, pancreatitis, osteoporosis, hyperhidrosis, multiple muscle ruptures, and hyperlipidemia. After a few days of disorientation and amnesia, the young female recovered completely. Clinical neurological examination was noticeable for partial ophthalmoparesis and mild hyperprolactinemia. She received an implantable cardioverter defibrillator, which did not discharge so far. Recurrent syncopes and aborted SCD may be the initial manifestation of MM with multiple organ involvement. The family history is important in cases with aborted SCD to guide the diagnostic work-up. Phenotypic heterogeneity between the family members may be an indicator of MM.